Unionization and Strategic Trade Policy - Swagel, Phillip; Tan, Ling. (Washington, D.C. : International Monetary Fund, 2000)
This paper examines the effect of unionization on welfare and trade policy in a model of duopolists competing in a third market. It shows that the traditional result that the presence of a union necessitates a stronger strategic trade policy to reach the optimal level of welfare depends on the mode of competition. With Bertrand duopolists, a union can be welfare-improving; it can also lead to a weaker trade policy, or even reverse the direction of the optimal policy. The results highlight the importance for trade policy of understanding the nature of firm behavior and the institutional features of the labor market.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet